A study from the perspectives of students and instructors about the cultural contexts of online learning in Chinese and Flemish higher education - TIE WEIFANG, TIE WEIFANG; DR. NIDHI AGARWAL , DR. NIDHI AGARWAL (International Journal of Multidisciplinary Research and Studies, 2024)
Learners' "Intercultural difficulties can have a major impact on students' ability to learn and their overall level of school involvement. An online classroom, says Hannon and D'Netto (2005), accentuates these impacts. Although it is feasible for e-learning to be culturally inclusive, this does not mean that cultural disparities, such as those involving students' preferences and perceptions of learning environments, are eradicated. It has been established by academics that there are 'cultural gaps' between those who are engaged in online learning (Chase et al., 2002). It has been found, for instance, that the prevalence of online communication varies significantly amongst cultural groups (Macfadyen, 2005). Taking students' cultural origins into account is crucial for analyzing the impact of social-constructivist e-learning "because students' cultural backgrounds shape their expectations, worldviews, and reactions. There has been a lack of empirical research on the effects of a socially constructive "e-learning environment" on various cultural contexts (Gribble &" Ziguras, 2003).